Limited indirect fitness benefits of male group membership in a lekking species. Issue 21 (16th October 2014) - Lebigre, Christophe; Alatalo, Rauno V.; Soulsbury, Carl D.; Höglund, Jacob; Siitari, Heli
Abstract In group living species, individuals may gain the indirect fitness benefits characterizing kin selection when groups contain close relatives. However, tests of kin selection have primarily focused on cooperatively breeding and eusocial species, whereas its importance in other forms of group living remains to be fully understood. Lekking is a form of grouping where males display on small aggregated territories, which females then visit to mate. As females prefer larger aggregations, territorial males might gain indirect fitness benefits if their presence increases the fitness of close relatives. Previous studies have tested specific predictions of kin selection models using measures such as group‐level relatedness. However, a full understanding of the contribution of kin selection in the evolution of group living requires estimating individuals' indirect fitness benefits across multiple sites and years. Using behavioural and genetic data from the black grouse (Tetrao tetrix), we show that the indirect fitness benefits of group membership were very small because newcomers joined leks containing few close relatives who had limited mating success. Males' indirect fitness benefits were higher in yearlings during increasing population density but marginally changed the variation in male mating success. Kin selection acting through increasing group size is therefore unlikely to contribute substantially to the evolution and maintenance of lekking in this black grouse population.